2014
DOI: 10.1111/ijfs.12580
|View full text |Cite
|
Sign up to set email alerts
|

The effects of heat–moisture treatment of rice grains before parboiling on viscosity profile and physicochemical properties

Abstract: The effects of heat-moisture treatment (HMT) (120°C for 10, 30 and 60 min) on paddy rice grains before parboiling, on head rice yield (HRY), pasting and thermal properties, and colour and cooking characteristics of parboiled rice were studied. The results indicated that the HMT performed intensifies the changes in grains after parboiling, impacting pasting and thermal properties, which results in rice kernels with yellowish colouration and greater cooking time. HMT increased the temperatures of gelatinisation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 26 publications
2
13
0
2
Order By: Relevance
“…The MT for 30, 45, and 60 min reduced ( p ≤ 0.05) setback of oat grains, as compared to native and 15 min‐HMT (Table ). A similar behavior was observed by Arns et al in rice grains subjected to HMT (120°C, 1 kPa, 60 min). This behavior might be the result of interactions between starch molecules, proteins, fatty acids and β‐glucan during HMT, which hinder the reapproximation of starch molecules.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The MT for 30, 45, and 60 min reduced ( p ≤ 0.05) setback of oat grains, as compared to native and 15 min‐HMT (Table ). A similar behavior was observed by Arns et al in rice grains subjected to HMT (120°C, 1 kPa, 60 min). This behavior might be the result of interactions between starch molecules, proteins, fatty acids and β‐glucan during HMT, which hinder the reapproximation of starch molecules.…”
Section: Resultssupporting
confidence: 88%
“…The HMT for 45 and 60 min reduced breakdown of oat grains when compared to the native ones (Table ). The reduction of breakdown promoted by HMT (120°C, 1 kPa, 60 min) in rice grains was also observed by Arns et al , and roasted oat flour in a hot air oven at 155°C for 30 min with 20% moisture was investigated by Hu et al . The reduction of breakdown demonstrates the presence of a paste more resistant to heating and mechanical stirring; this is probably due to a complexation of beta‐glucans, proteins and fatty acids with starch molecules that impedes the collapse of starch structures after formation of the paste.…”
Section: Resultsmentioning
confidence: 53%
“…Hogan and Plank (1958) suggested that the hydration characteristics of rice are influenced by variety and size of grain. Water uptake properties of rice grain directly relate with cooking time of the grain and longer cooking time shows higher internal restructuring of the grain (Arns et al 2014). Highest water uptake properties were found in RR2 (3.65 ± 0.01), and hence, optimal cooking time (31.16 ± 0.01 min) was also highest in RR2.…”
Section: Cooking Characteristicsmentioning
confidence: 99%
“…The treatment does not involve gelatinization and thus does not cause any damage to the granular structure . The method treats the starch granules at limited moisture levels (<35% moisture w/w) for 15 min to 16 h at temperatures above the gelatinization temperature (84–120°C) . The treatment promotes retrogradation and formation of RS3 .…”
Section: Modification Of Starchmentioning
confidence: 99%